VIOLÊNCIA CONTRA CRIANÇAS E ADOLESCENTES: A HISTÓRIA DESSA REALIDADE NA REGIÃO DO GRANDE ABC-SP - CARAVIERI, LÍGIA MARIA VEZZARO (2019)
Violence is a serious violation of the rights of children and teenagers, and although Brazilian legislation guarantees their full protection, this demographic continues to suffer repeated violations of their rights. Thus, the objective of this study is to describe and analyse the socio-demographic profile of children subjected to violence in the Great ABCD region, in the State São Paulo, relating their profiles with the historical evolution of the public policies that make up the System of Guarantee of Rights. The research is epidemiological, utilising methodological principles from descriptive and bibliographical research. The sample consisted of 1559 records of 2470 children and teenagers (ranging from zero to nearly 18 year olds) victims of violence assisted by the Regional Centre of Child Abuse Awareness in the ABCD region (CRAMI), currently called Ficar de Bem – CRAMI, between January 1993 and December 2017. The gathered data was statistically organised and described with frequencies and percentages, with a reliance rate of 95%. The results showed that physical violence was present in the majority of cases (57.7%), followed by negligence (37.8%). Regarding the sex of the victims, there was a certain equilibrium in the rates of violence, with the exception of sexual abuse rates, in which 77.9% of victims were female. Most victims were younger than seven years old (39.1%), the second largest group being between the ages of eight and eleven (34%), with teenagers coming in last (26.9%). The results also showed that mothers are the main perpetrators of physical (41.6%) and psychological (32%) violence, followed by fathers, showing respective rates of 29.3% and 29.4%. In cases of sexual violence the great majority of abusers were men (91.8%), fathers being the most frequent culprits (25.9%), followed by stepfathers (20.1%). In cases of negligence mothers were to blame for most violations, either acting alone (66.6%) or sharing the blame with the youth’s father (21.9%). Given this scenario, it is important that the epidemiological indicators analysed in this research are not perceived only as statistical data, but as a resource that can subsidize the implementation of public policies that ensure the protection and integral development of children and teenagers. The application of psychology in this process must occur in an interdisciplinary manner, considering the subjective aspects of the different forms of social organization and using Public Policies as a collective strategy for social change.